Effect of experimental hypersplenism on the erythropoiesis - Sukhomlinova, I. E.; Tihonovskaya, M. A.; Tihonovskiy, A. V.; Сухомлінова, Ірина Євгенівна; Тихоновська, Марина Анатоліївна; Тихоновський, Олександр Володимирович (Запорізький державний медичний університет, 2015)
Growth of the anemic conditions in clinical practice need to be improved in diagnosis, prevention and treatment of this disease. So one of the manifestations of the "hypersplenism" syndrome is an anemic development. According to various studies "hypersplenism" and regeneration of bone tissue accompanied by increassng of serotonin levels. Explanation of the mechanisms of anemia in the given pathologies are different and are not determined at present time. The aim of our study was to establish inhibition during experimental erythrocytosis.